Assessment Of Head Injury Criteria And Chest Severity Index For Frontal Impact - Salwani, Mohd Salleh; Sahari, B. B.; Aidy, Ali; Nuraini, A. A. (2014)
In this study, Head Injury Criteria (HIC) and Chest Severity Index (CSI) assessment are made based on the finite element simulation. Simulations are carried out through nonlinear finite element analysis software Ls-dyna. The effect of introducing aluminum alloy, AA5182 to automotive side member on the occupant injury is highlighted in comparison to the existing model made of steel. The HIC and CSI are taken as the evaluation criteria. The injury criteria is assessed under two impact conditions, that is full frontal and oblique impact. Aim of this paper to analyze the effect of lightweight materials on occupant crash protection. It was shown that the introduction of AA5182 provides great reduction in mass while improving the HIC and CSI performance during full frontal impact and only CSI in oblique impact.